Accurate and Precise Determination of Gold in Plating Bath Solution: Deep Eutectic Solvent Based Liquid Phase Microextraction – Slotted Quartz Tube – Flame Atomic Absorption Spectrometry. (22nd January 2020) - Yılmaz, Özge; Durak, Büşra Yılmaz; Tekin, Zeynep; Koçoğlu, Elif Seda; Bakırdere, Sezgin
Abstract: A sensitive, simple and green deep eutectic solvent based liquid phase microextraction (DES-LPME) method is described for the quantification of trace gold by flame atomic absorption spectrometry with a slotted quartz tube (SQT-FAAS). A 1:2 choline chloride:phenol mixture was utilized as the DES for the extraction of gold from the aqueous solution. All of the parameters affecting the extraction efficiency were optimized to increase the detection power of the FAAS. Under the optimum conditions, the presented method provided a linear range between 15 and 400 µg/L with limits of detection and quantification of 5.1 and 16.9 µg/L, respectively. An approximate 58-fold improvement was obtained in the detection power of the FAAS based on the limit of detection using the optimized DES-LPME-SQT-FAAS method. In order to check the validity/applicability of the method, recovery measurements were performed for spiked gold plating bath samples and the resulting recoveries were between 105.3% and 107.6%. The presented method was employed for real sample analysis.